Improving Learning Quality Through the Adoption of Interactive Digital Learning Models: A Case Study in Junior High Schools - Sihaloho, Fahmi Ashari S; Ashari, Novialdi; Sihaloho, Ulfah Oktarida; Harahap, Sarwedi; Pane, Muhammad Akbar Syahbana (Outline Journal of Community Development, 2025)
The development of human resources that are adaptive to the challenges of the 21st century demands a significant transformation in the education sector. This community service article aims to describe, implement, and analyze the effectiveness of an interactive digital learning model (IDLM) based on a Learning Management System (LMS) and mobile devices for core subjects (e.g., Science or Mathematics) at the Junior High School (JHS) level. This study is motivated by the finding that conventional learning is often less effective in fostering independent learning motivation and critical thinking skills among young adolescents. The service method uses an Action Research approach divided into three main cycles: planning, action, and reflection, involving 80 students and 10 teachers as partners. The IDLM implementation includes the development of digital content, interactive learning videos, and gamified assessments. The results of the service show a significant increase in the material retention index and the average score in post-intervention formative tests. Furthermore, in-depth interviews and participatory observation confirm a positive shift in students' attitudes, from passive to more proactive and collaborative in the learning process. The conclusion affirms that the structured and integrated adoption of technology acts as a catalyst for improving the quality of education, in line with the demands of the Industry 4.0 revolution.